EDUKASI ERGONOMI DAN MCKENZIE EXERCISE UNTUK PENCEGAHAN NYERI HERNIA NUCLEUS PULPOSUS PADA LANSIA PEKERJA INDUSTRI TAHU - Dewi Kahesti; Evrilia Shifaul Qolbi; Farras Putri Khairiyah; Gita Gita; Hafizatul Athalia; Muhammad Fathurramadhan; Salma Agustia Pramesti; Tegar Pamungkas; Hapsari Cahyaningrum (Jurnal Padamu Negeri, 2026)
Herniated Nucleus Pulposus (HNP) is a condition that affects the spine and often causes pain in the lower back, especially in elderly individuals engaged in heavy physical work. Many elderly workers in a tofu factory in Tegalwedan Village, Tegalgondo, Wonosari, Klaten, complain of lower back pain. Unergonomic working positions and a lack of knowledge about HNP prevention are among the causes of back pain. This community service program aims to increase public awareness of HNP by providing education on the definition, symptoms, risk factors, and ways to prevent pain through the application of ergonomic techniques and McKenzie Exercises. The methods used included delivering information through presentations, exercise demonstrations, and distributing leaflets to 30 participants. Evaluation was conducted using pre- and post-tests. The pre-test results indicated that participants' knowledge was still low, with many unfamiliar with HNP, risk factors, signs and symptoms, ways to reduce pain, or ergonomic work positions. After conducting community education, the results showed an increase in participant knowledge, where the average pre-test score of 16.1% increased to 73.9% in the post-test, resulting in an increase of 57.8%. Ergonomic education and McKenzie Exercise training were effective in improving the knowledge and skills of the elderly in preventing HNP pain. It is hoped that this program can be implemented sustainably by health cadres and the community to support better behavior changes in maintaining musculoskeletal health.